Identification and characterization of a novel thermohalophilic esterase from the Red Sea: Atlantis II brine pool - Mohamed, Yasmine Mustafa (AUC Knowledge Fountain, 2011)
Industrial (white) biotechnology poses an increasing demand for novel biocatalysts that are robust under a wide range of conditions. Traditionally, biocatalysts were isolated from cultured isolates, however, less than 1% of microorganisms are culturable. Therefore, it became evident that the unculturable majority holds a great potential for the discovery of novel biocatalysts. Metagenomics is an invaluable tool for accessing the genomes of the uncultured majority and has led to the isolation of a large number of biocatalysts from various environments. Extreme environments such as hydrothermal vents, brine pools and glaciers, are an attractive source for biocatalysts. Biocatalysts from these environments almost always reflect in their characteristics the environment from which they originated, and therefore may exhibit high stability and activity in the aggressive conditions required by some processes. The Atlantis II deep is a brine pool in the Red Sea and is characterized by high temperature (almost 70oC), high salinity (7.5 times that of normal sea-water), high metal concentration and anoxia. Such extreme conditions make the Atlantis II deep an attractive site for mining for biocatalysts. Using lipolytic enzymes as biocatalysts in industrial and biotechnological processes is estimated to be a billion dollar business. Their applications in industry include, and are not limited to, biodiesel formation, pulp and paper industry, detergent industry and flavor development and therefore, the demand for novel lipolytic enzymes is increasing continuously. Several studies attempted to, and successfully isolated novel lipolytic enzymes with unique characteristics using metagenomic approaches. However, the Atlantis II deep was not previously mined for lipolytic enzymes. In this study, samples were collected from the Atlantis II deep and were used for the construction of a large-insert fosmid clone library. The library was screened for lipolytic activity using a function-based approach. Sequencing of positive clones identified a novel lipolytic enzyme (EstATII), which was then subcloned from the original fosmid into a high copy number plasmid to allow simple overexpression and characterization of the enzyme. Characterization of EstATII revealed that it's a novel thermophilic (optimum temperature = 60oC) and halophilic esterase, with potential applications in processes requiring extreme conditions such as biodiesel production and resolving of racemates.